2020
DOI: 10.1101/2020.12.16.423054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of protein N-myristoylation blocksPlasmodium falciparumintraerythrocytic development, egress, and invasion

Abstract: We have combined chemical biology and genetic modification approaches to investigate the importance of protein myristoylation in the human malaria parasite, Plasmodium falciparum. Parasite treatment during schizogony in the last ten to fifteen hours of the erythrocytic cycle with IMP-1002, an inhibitor of N-myristoyl transferase (NMT), led to a significant blockade in parasite egress from the infected erythrocyte. Two rhoptry proteins were mislocalized in the cell, suggesting that rhoptry function is disrupted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The enzyme NMT is expressed throughout the Plasmodium life cycle and is a promising target for antimalarial drug development. Schlott et al (2021) showed that NMT inhibition disrupts at least 3 vital pathways of the parasite lifecycle: early schizont development, merozoite formation, and merozoite egress (15). Despite this promise, the enzyme has been deprioritized as an antimalarial target due to challenges in identifying parasite-selective inhibitors and a slow mechanism of action (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme NMT is expressed throughout the Plasmodium life cycle and is a promising target for antimalarial drug development. Schlott et al (2021) showed that NMT inhibition disrupts at least 3 vital pathways of the parasite lifecycle: early schizont development, merozoite formation, and merozoite egress (15). Despite this promise, the enzyme has been deprioritized as an antimalarial target due to challenges in identifying parasite-selective inhibitors and a slow mechanism of action (16).…”
Section: Discussionmentioning
confidence: 99%
“…also report high-affinity compounds that kill blood- and liver stage parasites; Pf NMT with an IC 50 value of 8 nM, up to fourfold selectivity over Hs NMT1/2, P. falciparum blood stage EC 50 value of 302 nM, and P. berghei liver stage EC 50 value of 372 nM ( 14 ). Pharmacological inhibition of NMT prevents the completion of blood-stage development of P. falciparum partly owing to the inhibition of the inner membrane complex formation ( 15 ). Thus, selective targeting of NMT could aid in the development of a drug that targets multiple life cycle stages.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, as malaria parasites can be targeted within mosquitoes, e.g., through mosquito uptake of antiparasitic drugs (Paton et al , 2019), it might be feasible to target the parasite cell shape maintenance pathways with small molecules within the insect to prevent the transmission of the parasite. While concavin might not directly be targetable, enzymes involved in overall cell shape maintenance such as palmitoyl transferases (Wang et al , 2005; Santos et al , 2015; Hopp et al , 2021; Schlott et al , 2021) could be good candidate targets.…”
Section: Discussionmentioning
confidence: 99%
“…GAP45 is thought to maintain the interaction between the IMC and the plasma membrane, and acts as an essential bridge between the two structures 102 . Deleting GAP45 has been proved to prevent glideosome assembly in P. falciparum 103 . Perhaps the absence of GAP45 in gregarines and Cryptosporidium could be compensated by other GAP-like proteins or it may not even be necessary.…”
Section: The Model Machinery May Be Partially Compensated By Alternat...mentioning
confidence: 99%